Utilizing Organic Waste (Sugarcane Bagasse and Sugarcane Leaves) as Bio Briquettes through Pyrolysis Process - Saputro, Erwan Adi; Billah, Mu’tasim; Laksminingsih, Arieanthi; Mardiansyah, Yuda Eka; Yogaswara, Rachmad Ramadhan; Erliyanti, Nove Kartika (Future Science)
The energy crisis is approaching, not only Indonesia but also all around the world. This requires technological innovation to overcome it, such as; making alternative fuels that are cheap and easy to produce. One alternative way to overcome this problem is to make alternative fuels in the form of bio briquettes by utilizing organic waste (sugarcane bagasse and sugarcane leaves). This study aims to study the effect of the ratio of leaves and bagasse as main sources and using lignin as the adhesive, to produce bio briquettes. The ratio of leaves and bagasse used in this research were (30: 70). The pyrolysis process is carried out to obtain charcoal and sieved at 30 mesh. The charcoal is then mixed with the adhesive. The ratio of the amount of lignin with a mixture of sugarcane bagasse and leaves were (10: 90); (15: 85); (20: 80); (25: 75); (30: 70), and mold. The briquettes formed dried in an oven at 105 oC for 1 hour. The results of this study showed that the lowest calorific value was 4860 cal/kg at 10% lignin content and the highest calorific value at 25% was 5876 cal/kg. The results of the analysis of the lowest moisture content (%) were at 10% lignin content of 0.0781% and the highest moisture content was 0.1387% at 25% lignin content.